Selective catalytic reduction of NOₓ in marine engine exhaust gas over supported transition metal oxide catalysts - Jia, Chunmiao (2022)
The selective catalytic reduction (SCR) of nitrogen oxides (NOx) in the presence of methanol (methanol-SCR) was investigated over commercial oxide (γ-Al2O3 and TiO2) supported transition-metal oxide catalysts in lab scale. Of all the prepared catalysts, CuO/γ-Al2O3 catalyst exhibited the highest reduction efficiency in the methanol-SCR process. The practical test results in a marine engine further showed that the 2 wt% CuO/γ-Al2O3 catalyst can remove 93.9% of NOx without catalyst deactivation in several hours. Evidenced by relevant characterization results, the fast-redox properties of copper and rich acidic sites of γ-Al2O3 support were responsible for the excellent catalytic activity of the CuO/γ-Al2O3 catalyst. Revealed by In-situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS), formate-like species derived from methanol dehydrogenation act as the reaction intermediates for NOx reduction. Moreover, this work provides a novel process to reduce NOx and make use of adverse hydrocarbons in the flue gas simultaneously, opening a new research direction in NOx reduction technologies.